The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1097/00005768-200012000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in a predominantly African-American group of stroke survivors

Abstract: A supervised exercise training program for stroke survivors with multiple comorbidities was highly effective in improving overall fitness, potentially reducing the risk of further disease and disability. Greater effort must be made on the part of the public health community to increase access to community-based physical activity programs for persons with stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 23 publications
2
88
0
1
Order By: Relevance
“…18 Compared with controls, the exercise group demonstrated significant gains in peak oxygen uptake and strength and improvements in body composition.…”
Section: Effects Of Exercise Training and Rehabilitation Programs In mentioning
confidence: 92%
See 1 more Smart Citation
“…18 Compared with controls, the exercise group demonstrated significant gains in peak oxygen uptake and strength and improvements in body composition.…”
Section: Effects Of Exercise Training and Rehabilitation Programs In mentioning
confidence: 92%
“…11 In the context of defining therapy goals for the poststroke patient, it is essential that the family be integrated into the process as early as possible. Early involvement of the family unit has been strongly correlated with patient adherence to therapy, better understanding between patient and caregiver of achievable outcomes, and improved communication between patient and • 40%-70% peak oxygen uptake; 40%-70% heart rate reserve; 50%-80% maximal heart rate; RPE 11-14 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) caregivers. 79 To facilitate optimal outcomes from an exercisebased stroke rehabilitation program, an assessment of familial support should be undertaken.…”
Section: Barriers To Physical Activity and Exercise Training In Strokmentioning
confidence: 99%
“…However, few studies have specifically assessed the effects of exercise training on markers of CVD risk in the stroke population [16]. Rimmer et al reported that exercise training improved dyslipidemia and measures of regional adiposity in morbidly obese individuals with stroke (mean body mass index [BMI] >35) [54]. Additionally, Fletcher et al reported that a home exercise training program improved left ventricular ejection fraction and lipid profiles in chronically disabled individuals, the majority of whom were individuals with stroke [55].…”
Section: Effects Of Treadmill Training On Markers Of Cardiovascular-mmentioning
confidence: 99%
“…People with stroke are especially vulnerable to the effects of a sedentary lifestyle and would benefit greatly from increasing the amount of physical activity they regularly obtain [9][10][11][12][13]. Unfortunately, options for exercise and recreation are often limited by numerous personal (e.g., motivation, self-efficacy) [14][15] and environmental or facility barriers (e.g., inaccessible programs, equipment, and services offered in community recreation facilities) [16].…”
Section: Introductionmentioning
confidence: 99%